Strategic Brand Positioning in the Digital Marketplace: Insights from Emerging Businesses - Budiarti, Anindhyta (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
In the digital era, brand positioning has become a crucial factor for growing businesses to compete in the increasingly competitive digital marketplace. This study aims to identify the main factors and effective strategies used by growing businesses in building their brand position in the digital market. Using a qualitative approach, this study analyzes various case studies of businesses that have successfully implemented strong positioning strategies through the use of digital technology. The results show that product and service differentiation, brand credibility, and innovative digital marketing strategies are key factors in brand positioning. In addition, the use of social media, search engine optimization (SEO), influencer marketing, and data-driven marketing personalization have proven effective in increasing brand awareness and consumer engagement. The practical implications of this study highlight that growing businesses need to adopt flexible and data-driven marketing strategies to adapt to changes in consumer behavior in the digital environment. Active interaction with customers, building digital communities, and transparency in communication are important elements in building customer loyalty and strengthening brand positioning. From an academic perspective, this study contributes to digital marketing theory by emphasizing the importance of digital experiences and consumer engagement in shaping brand image. As a recommendation, businesses need to continue exploring digital marketing innovations and utilizing artificial intelligence and data analytics technologies to improve the effectiveness of their positioning strategies. Meanwhile, further research can explore the impact of cultural factors and technological developments on brand positioning strategies across industries. With the right approach, growing businesses can create sustainable competitive advantages and strengthen their presence in the dynamic digital marketplace.